2012
DOI: 10.1111/j.1365-3059.2012.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of populations of Rhizoctonia solani AG‐4 from five provinces in Iran

Abstract: Rhizoctonia solani anastomosis group 4 (AG-4) is a serious pathogen causing damping off and root rot in many important crop plants. A total of 190 isolates of R. solani AG-4 HG-I were collected from host fields in five provinces of Iran. The genetic structure of this pathogen was evaluated using seven microsatellite loci, focusing particularly on geographic differentiation. Most of the multilocus genotypes (MLGTs) were unique, with few MLGTs shared among populations. High to moderate levels of gene flow among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Additionally, Tuncer and Eken (2013) found that more than three quarters of the 81 R. solani isolates obtained from peppers grown in Erzincan province, Turkey belonged to AG-4. Alike, the most common occurrence of R. solani AG-4 isolates on cucumber, pepper and snap bean plants has also been reported from other countries by several workers (MIRMAJLESSI et al, 2012;HARATIANA et al, 2013). Colony characteristics of isolates belonging to R. solani AG-4 were found to be similar to those of other studies (SNEH et al, 1991;ERPER et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, Tuncer and Eken (2013) found that more than three quarters of the 81 R. solani isolates obtained from peppers grown in Erzincan province, Turkey belonged to AG-4. Alike, the most common occurrence of R. solani AG-4 isolates on cucumber, pepper and snap bean plants has also been reported from other countries by several workers (MIRMAJLESSI et al, 2012;HARATIANA et al, 2013). Colony characteristics of isolates belonging to R. solani AG-4 were found to be similar to those of other studies (SNEH et al, 1991;ERPER et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…R. solani is found on bean, cucumber, eggplant, pepper and tomato, which are important vegetable crops. In addition, R. solani can cause several types of damage, including dampingoff, root rot and web blight on bean (MUYOLO et al, 1993;KARACA et al, 2002;DEMIRCI, 2004;ERPER et al, 2011), damping-off and root rot on cucumber HARATIANA et al, 2013;JAISWAL et al, 2014), brown spot on eggplant (SNEH et al, 1991), damping-off, hypocotyl rot and root rot on pepper (KARACA et al, 2002, VELÁSQUEZ;VICTORIANO, 2007;LOPEZ et al, 2009;TUNCER;EKEN, 2013) and damping-off, foot and root rot on tomato MISAWA;KUNINAGA, 2010;SOLANKI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the average level of genetic differentiation Φst = 0Á159, and the presence of several shared multilocus genotypes among populations, indicate that migration has had an important role in the shaping of the population structure of FORL, with increases in the effective population size and the genetic diversity. High-to-moderate gene flow was reported for Rhizoctonia solani, where multilocus and LD analysis are consistent with a sexually recombining structure or with a mixed reproductive mode, depending on the populations; this includes both asexual and sexual reproduction, with some populations that showed evidence of inbreeding (Ferrucho et al, 2013;Haratian et al, 2013;Shu et al, 2014). These observations can be relevant for plant breeding.…”
Section: Discussionmentioning
confidence: 75%
“…be virulent to common bean in the pathogenicity test performed under controlled conditions. AG 4 had previously been reported to be the prevalent group associated with root and hypocotyl rot in other common bean growing areas worldwide (Muyolo et al, 1993;Meinhardt et al, 2002;Nerey et al, 2010;Kiliçoğlu and Özkoç, 2013;Haratian et al, 2013). In Zaire, isolates obtained from diseased dry bean roots and hypocotyls were characterized as AG 4 based on anastomosis-group determination using tester strains (Muyolo et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In Zaire, isolates obtained from diseased dry bean roots and hypocotyls were characterized as AG 4 based on anastomosis-group determination using tester strains (Muyolo et al, 1993). Most of the R. solani isolates recovered from bean plants showing root and hypocotyl rot symptoms collected in Brazil, Cuba, Iran and Turkey were characterized as AG 4 HG-I based on different techniques including sequencing of the rDNA-ITS region (Meinhardt et al, 2002;Nerey et al, 2010;Kiliçoğlu and Özkoç, 2013;Haratian et al, 2013). AG 4 isolates have also been reported to be associated with web blight in common bean (Gálvez et al, 1989;Tu et al, 1996;Godoy-Lutz et al, 2003Yang et al, 2007;Dubey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%